Novel Virulence Role of Pneumococcal NanA in Host Inflammation and Cell Death Through the Activation of Inflammasome and the Caspase Pathway - Tseng, Yu-Wen; Chang, Chun-Chi; Chang, Yung-Chi (Frontiers in Cellular and Infection Microbiology, 2021)
Streptococcus pneumoniae is one of most deadly Gram-positive bacterium causing significant mortality and morbidity worldwide. Intense inflammation and cytotoxicity is a hallmark of invasive pneumococcal disease. Pneumococcal NanA has been shown to exaggerate the production of inflammatory cytokines via unmasking of inhibitory Siglec-5 from its sialyl cis-lignads. To further investigate the mechanistic role of NanA and Siglec-5 in pneumococccal diseases, we systemically analyzed genes and signaling pathways differentially regulated in macrophages infected with wild type and NanA-deficient pneumococcus. We found that NanA-mediated desialylation impairs the Siglec-5-TLR-2 interaction and reduces the recruitment of phosphatase SHP-1 to Siglec-5. This dysregulated crosstalk between TLR-2 and inhibitory Siglec-5 exaggerated multiple inflammatory and death signaling pathways and consequently caused excessive inflammation and cytotoxicity in the infected macrophage. Collectively, our results reveal a novel virulence role of NanA in pneumococcal pathogenesis and suggest that targeting NanA activity may ameliorate the pneumococcus-mediated inflammation and cytotoxicity in severe invasive pneumococcal diseases.